2017
DOI: 10.15640/ijat.v5n2a3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Profitability, Leverage, Firm Size and Capital Intensity Towards Tax Avoidance

Abstract: This study aims to examine the factors that affect the company's tax avoidance. There are several factors used include size, leverage, profitability, and capital intensity. The purpose of this study is to determine the influence of firm size, leverage, profitability and capital intensity ratio on tax avoidance in manufacture companies listed on the Indonesian Stock Exchange 2013-2015. Population taken as the object of observation amounted to 156 manufacturing companies listed in Indonesia Stock Exchange in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
48
8
54

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 5 publications
16
48
8
54
Order By: Relevance
“…It is negative and therefore, the larger the company, the lower the ETR. This result is in line with Irianto et al (2017), Janssen (2005), and Richardson and Lanis (2007). It supports the "political power theory" (Siegfried, 1972).…”
Section: Sectorsupporting
confidence: 85%
See 1 more Smart Citation
“…It is negative and therefore, the larger the company, the lower the ETR. This result is in line with Irianto et al (2017), Janssen (2005), and Richardson and Lanis (2007). It supports the "political power theory" (Siegfried, 1972).…”
Section: Sectorsupporting
confidence: 85%
“…Thus, the related research hypotheses (H 2 and H 3 ) are confirmed. The result concerning the first variable is in line with Delgado et al (2018), Irianto et al (2017), Liu and Cao (2007). Most previous studies (Gupta and Newberry, 1997;Richardson and Lanis, 2007) that did not directly control for the effect of tax benefits envisaged to incentivise the investment in tangible fixed assets initially hypothesised and later found that a statistically significant and negative association exists between the incidence of tangible fixed assets and the ETR.…”
Section: Parametersupporting
confidence: 76%
“…With these conditions, the company will try to maintain its business cash flow instead of making tax payments. Furthermore, the use of variable leverage conducted by [9] shows that leverage has a negative effect on tax avoidance in addition to that research with similar variables that have been conducted by [5] The results of this study indicate that there is an influence between leverage and tax avoidance. Then corporate governance variables are used as one of the variables in research such as research conducted by [4] because, in the study, it stated that corporate governance has a positive influence on tax avoidance.…”
Section: Introductionsupporting
confidence: 64%
“…Kepemilikan aset tetap akan berpengaruh pada pengurangan pembayaran pajak yang akan dibayarkan oleh perusahaan, karena aset tetap menyebabkan adanya biaya depresiasi. Rasio intensitas modal sering dikaitkan dengan seberapa besar aktiva tetap dan saham yang dimiliki oleh perusahaan (Irianto, Sudibyo, & Wafirli S.Ak, 2017).…”
Section: Capital Intensityunclassified